Some recent German fairy-tales - Holmberg, Edith Antonia (My University, 1908)
Introduction: The following fairy-tales are a translation from the German and are taken from August Sherl’s “Neuer Deutscher Marchenschatz.” These stories were the result of a prize-contest at Berlin in which four-thousand and twenty-five contestants participated. Out of the one hundred stories submitted by the committee thirty of the best were sent to the judges.
Citation: Holmberg, Edith Antonia. Some recent German fairy-tales. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Fairy Tales; German Literature; Translations; Handwritten; Graduating theses; Senior theses; Theses